Peran Pemuda dalam Membangun Moralitas Keagamaan di Masyarakat - Utomo, Galih Priyo; Witasari, Rinesti (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Youth is part of the community which the community itself is expected to play a role in providing useful participation for the progress of society. Religious morality is an important thing to be built in the midst of society because religious morality leads people to actions that are in accordance with the good values of religious teachings. This research uses a qualitative case study approach. The techniques used in data collection are observation, interviews and documentation. The data analysis technique used is the concept of Miles & Huberman that the data is analyzed with theories that are relevant to the discussion. The objects used as informants in the study were five youths and one religious leader in the neighborhood of Rt 002, Rw 001, Kambangrejo Hamlet, Bedingin Village, Sambit District, Ponorogo Regency. The purpose of this study was to determine the role of youth in building religious morality in the community in that environment. The results of the study show that the youth of Rt 002, Rw 001, Dukuh Kambangrejo have a role in building religious morality in the community including participating in religious activities in the community such as yasinan, tahlilan, recitation, prospering mosques, being an example in cohesiveness, harmony, order, being a driving force for the community to creative, active in Ramadan activities such as tarawih prayers, tadarus quran, takbiran, and during Eid al-Adha, as well as maintaining environmental security.